Innovating Interprofessional Continuing Professional Development: Applying the Community of Inquiry Framework to Digital Learning Platforms - Manganello, Flavio; Aleo, Giuseppe (International Review of Research in Open and Distributed Learning, 2026)
This study investigated how the community of inquiry (CoI) framework can inform digital platform design for interprofessional continuing professional development (ICPD) in healthcare. Using a three-stage comparative methodology, we analyzed technological tools from foundational CoI literature (stage 1), conducted a rapid review of current digital ICPD practices (stage 2), and synthesized findings through matrix-based comparison (stage 3). The analysis of 10 foundational CoI studies and 11 digital interprofessional education studies revealed four distinct adaptation patterns: (a) technological convergence in core communication tools (asynchronous forums, Learning Management System (LMS) platforms); (b) evolutionary divergence in collaborative technologies (video conferencing, real-time document sharing); (c) implementation gaps in reflective and scaffolding tools; and (d) professional context adaptations addressing healthcare-specific needs. While current ICPD practices have demonstrated strong alignment with CoI principles in communication and collaboration tools, significant gaps exist in structured reflection mechanisms, automated feedback systems, and adaptive facilitation features. Critically, systematic CoI framework application in authentic ICPD contexts with practicing professionals has remained largely unexplored, with studies predominantly focused on pre-licensure interprofessional education. Current implementations have used CoI retrospectively as an analytical framework rather than proactively for design guidance. These findings suggest selective rather than comprehensive CoI integration in professional continuing education contexts. The study provided preliminary theoretical guidance for enhancing digital ICPD through CoI-informed design while highlighting the urgent need for empirical validation with practicing healthcare professionals.